2005
DOI: 10.1212/01.wnl.0000162036.76024.ab
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating progression in ALS

Abstract: The authors prospectively studied the value of clinical and neurophysiologic measurements in assessing progression in ALS. Motor unit number estimation (MUNE) and the neurophysiologic index (NI) were significantly correlated with ADM strength (maximal voluntary isometric contraction force in the abductor digiti minimi muscle [MVIC-ADM]). MUNE and the NI were reliable, but the NI showed a lower variation. On assessing progression at 3, 6, and 12 months, MUNE, NI, and MVIC-ADM showed the highest rate of change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…A Keypoint machine (Dantec, Skovlunde, Denmark) was used for the neurophysiological studies. The temperature of the Abbreviations: ADM, abductor digiti minimi muscle; ALS, amyotrophic lateral sclerosis; ALS-FRS, amyotrophic laterals sclerosis functional rating scale; CSP, cortical silent period; CMAP, compound muscle action potential; EMG, electromyogram; FVC, forced vital capacity; LMN, lower motor neuron; MEP, motor evoked potential; MUNE, motor unit number estimation; MRC, Medical Research Council (UK); NI, Neurophysiological Index; UMN, upper motor neuron Correspondence to: M. de Carvalho; e-mail: mamedemg@mail.telepac.pt investigated limb was kept at 32 C. Motor unit number estimation (MUNE), 2,3 the Neurophysiological Index (NI), 3 and transcranial magnetic stimulation (TMS) 6 were evaluated at each test session. For MUNE measurements we used the incremental technique.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Keypoint machine (Dantec, Skovlunde, Denmark) was used for the neurophysiological studies. The temperature of the Abbreviations: ADM, abductor digiti minimi muscle; ALS, amyotrophic lateral sclerosis; ALS-FRS, amyotrophic laterals sclerosis functional rating scale; CSP, cortical silent period; CMAP, compound muscle action potential; EMG, electromyogram; FVC, forced vital capacity; LMN, lower motor neuron; MEP, motor evoked potential; MUNE, motor unit number estimation; MRC, Medical Research Council (UK); NI, Neurophysiological Index; UMN, upper motor neuron Correspondence to: M. de Carvalho; e-mail: mamedemg@mail.telepac.pt investigated limb was kept at 32 C. Motor unit number estimation (MUNE), 2,3 the Neurophysiological Index (NI), 3 and transcranial magnetic stimulation (TMS) 6 were evaluated at each test session. For MUNE measurements we used the incremental technique.…”
Section: Methodsmentioning
confidence: 99%
“…For MUNE measurements we used the incremental technique. 3 The NI is derived from conventional neurophysiological measurements, including M-wave amplitude, distal motor latency, and F-wave frequency in the ulnar territory using the formula: (M-wave amplitude/distal motor latency) Â (Fwave responses per 20 stimuli). 3 Both right and left ulnar nerve-ADM nerve-muscle systems were studied in each subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In that ALS population, the decline in strength of individual muscles correlated well with the decline in MUNE counts. Questions remain, however, as to whether it is valid to extrapolate from a small number of muscles to the overall neuromuscular function of an individual.…”
Section: Discussionmentioning
confidence: 75%
“…Other problems with MUNE include the technical difficulty of performing such studies and the variability of the data obtained. Only one study has shown an association between MUNE and strength of individual muscles, 6 and an association of MUNE with overall neuromuscular function has not been demonstrated.…”
mentioning
confidence: 99%